Microfluidic Bio-Sensors and Their Applications - Kant, Krishna (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint will help young readers discover systematic research and reviews of the various topics in the field of microfluidic-based biosensing. This reprint contains empirical studies and systematic reviews regarding the use of microfluidic technology in biosensing and its applications in point-of-care system development.